2022
DOI: 10.1111/ene.15413
|View full text |Cite
|
Sign up to set email alerts
|

Sudomotor dysfunction in people with neuromyelitis optica spectrum disorders

Abstract: Background and purpose The aim was to determine the extent of sudomotor dysfunction in people with neuromyelitis optica spectrum disorder (pwNMOSD) and to compare findings with a historical cohort of people with relapsing–remitting multiple sclerosis (pwRRMS). Methods Forty‐eight pwNMOSD were enrolled from four clinical centers. All participants completed the Composite Autonomic Symptom Score 31 to screen for symptoms of sudomotor dysfunction. Sudomotor function was assessed using the quantitative sudomotor ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In recent years, research on autonomic dysfunction in NMOSD patients has been obtained. Two studies compared autonomic dysfunction between patients with NMOSD and those with MS [ 12 , 13 ], finding a significant proportion of NMOSD patients suffered autonomic dysfunction and were more often symptomatic than MS patients in certain domains of dysautonomia. Another study suggested 74.1% of patients with NMOSD suffered dysautonomic symptoms and investigated the correlated clinical and MRI factors of dysautonomia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on autonomic dysfunction in NMOSD patients has been obtained. Two studies compared autonomic dysfunction between patients with NMOSD and those with MS [ 12 , 13 ], finding a significant proportion of NMOSD patients suffered autonomic dysfunction and were more often symptomatic than MS patients in certain domains of dysautonomia. Another study suggested 74.1% of patients with NMOSD suffered dysautonomic symptoms and investigated the correlated clinical and MRI factors of dysautonomia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on autonomic dysfunction in NMOSD patients has been obtained. Two studies compared autonomic dysfunction between patients with NMOSD and those with MS (12,13), nding a signi cant proportion of NMOSD patients suffered autonomic dysfunction and were more often symptomatic than MS patients in certain domains of dysautonomia. Another study suggested 74.1% of patients with NMOSD suffered dysautonomic symptoms and investigated the correlated clinical and MRI factors of dysautonomia (14).…”
Section: Introductionmentioning
confidence: 99%